IMAGE PROCESSING / AUGMENTATION WITH SCIKIT-IMAGE PYTHON LIBRARY - Agung Slamet Riyadi; Dhian Sweetania; Puji Sularsih (Dinamika Dotcom : Jurnal Pengembangan Manajemen Informatika dan Komputer, 2022)
Deep Learning is the development of Machine Learning technology that uses algorithms based on mathematical laws. This algorithm works like the human brain. One of the uses of Deep Learning is in the field of digital image processing or Image Processing. Humans use image processing to help identify and / or classify objects quickly and accurately, and can process a lot of data at the same time. Convolutional Neural Network (CNN) is one of the deep learning algorithms used in image processing. Convolutional layer, pooling layer and fully connected layer are the 3 main layers of the CNN Algorithm. Convolutional Neural Network (CNN) groups images into two stages, namely the training and testing stages. In the training phase, CNN learns about extracting features from each data to distinguish a tag from other tags. In the testing phase, the tested data will be analyzed from the results of the training phase. The purpose of this study is to use the Convolutional Neural Network method to classify organic waste and recycle waste (recyclable waste).